Folate affects neural tube development through KDM6A - GAO Jun, LI Jian-ting, XIE Qiu, ZHANG Yong-feng, QIAO Li-na, LIU Chang-yun, WANG Jian-hua (Jichu yixue yu linchuang, 2020)
Objective To investigate the effects of lysine-specific demethylase 6A (KDM6A) on neural tube defects (NTDs) in low folate environment. Methods Mouse embryonic stem cells (SV129), NTD mouse models and NTD human specimens were used. SV129 cells were incubated with 0.02 μmol/L methotrexate (MTX) for 24 h, and the folate level was measured by Access 2 Immunoassay system and competitive receptor binding immunoassay. DNA fragmentation and KDM6A expression were detected by Western blot and immunofluorescence. The transcription level of the DNA fragment-related repair gene was measured using the mouse NTD model. The folate content and the expression of KDM6A in human NTD specimens were examined. Results In the low folate environment, the DNA fragmentation increased and the expression of KDM6A protein decreased. At the same time, the expression of DNA fragment repair gene KU80/70 in mouse NTD model decreased (P＜0.05); the expression of low folate NTD specimen KDM6A and KU80 also decreased. Conclusions In a low folate environment, DNA fragmentation increases and KDM6A expression decreased, which may initiate abnormal DNA repair pathways and lead to NTD.